Implementation of Using Imagination Learning Techniques in an Effort to Improve The Competence of Writing Poetry in Grade X SMA N 1 Padang Bolak Julu, North Padang Lawas - Lubis, Rodiah; Sutikno (International Journal of Educational Research Excellence (IJERE), 2025)
The problems in this research are: 1) what are the results of the ability to write poetry by class X students of SMA Negeri 1 Padang Bolak Julu for the 2024-2025 academic year using imagination techniques?; 2) What is the process of applying imagination techniques to improve the ability to write poetry by class X students of SMA Negeri 1 Padang Bolak Julu?. The subjects in this research were class X students of SMA Negeri 1 Padang Bolak Julu for the 2024-2025 academic year, totaling 40 people. Meanwhile, the object of this research is the results of students' poetry writing abilities. The instrument used in data collection was a multiple choice test. The results of the research showed that by using imagination techniques the results of students' poetry writing abilities increased from cycle I to cycle III, through the average of students' poetry writing abilities, namely learning outcomes tests I, II and III. From cycle I to cycle II students' ability to write poetry increased from 64 to 72.5, an increase of 8.5, likewise from cycle II to cycle III it increased from 72.5 to 83.16, an increase again of 10.66. Logically from cycle I to cycle III it increases by 19.6. Likewise, the students' learning completeness in the first cycle of students who completed their learning was 47.5%, when compared with the criteria for the level of learning completeness, it was below the criteria. Then it rose to 72.5% in cycle II. In cycle III, learning completeness had reached 87.5%, when compared with the criteria, the level of learning completeness was at good criteria. Thus the hypothesis proposed previously can be accepted as true